2016
DOI: 10.5901/mjss.2016.v7n4s2p163
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 8 Weeks Rhythmic Aerobic Exercise on Vaspin Levels and Lipid Profile in Overweight and Obese Women

Abstract: Obesity as a chronic disease causes many diseases. Vaspin is a new adipokine, which increase as a result of inflammation resulting from obesity and metabolic diseases (3). Regular exercise has a variety of benefits, including increasing insulinsensitivity, controlling blood sugar (glucose), losing weight, decreasing body fat percentage, reducing inflammation stress. Kadoglou et al. (2013) (P = 0.000), vaspin (P = 0.003), HDL (P = 0.000), LDL (P = 0.001), and TC (P = 0.001), while had no significant effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…and Shahdadi et al. 135 , 149 showed a reduction in serum vaspin levels after AT in obese subjects. In contrast, a higher vaspin level has been found following 4-week AT in obese and T2D subjects.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…and Shahdadi et al. 135 , 149 showed a reduction in serum vaspin levels after AT in obese subjects. In contrast, a higher vaspin level has been found following 4-week AT in obese and T2D subjects.…”
Section: Introductionmentioning
confidence: 91%
“…Similar to AT, vaspin serum level is changed differently in response to RT. For example, two studies reported a significant reduction in serum vaspin level following RT in obese individuals, 135 , 149 in contrast with Mahdirejei et al. 150 who reported no significant alteration.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…280 Similarly, other studies reported significant decreases in vaspin levels after rhythmic aerobic exercise or rhythmic aerobic exercise plus core stability training in females with overweight and/or obesity. 277,281,282 However, a cross-sectional study found no significant differences in vaspin levels between control adolescent male subjects and individuals with obesity (BMI ≥ 25) subjected to 12 weeks of aerobic exercise. 283 However, vaspin levels were significantly associated with intima-media thickness, an early indicator of atherosclerosis.…”
Section: Effects Of Acute and Chronic Exercise On Vaspinmentioning
confidence: 99%